Penetrating Fish-Hook Ocular Injury: Management of an Unusual Intraocular Foreign Body. (13th April 2014) - Iannetti, Ludovico; Tortorella, Paolo
Abstract : Importance . Ocular penetrating fish-hook injuries represent an unusual and very dangerous ocular trauma. We report the management of an unusual case of a simple-single barbed fish-hook accident globe injury successfully treated with surgery. Observations . We described a case report of a caucasian 32-year-old man presented with a scleral perforation of the left eye caused by a fish-hook injury while fishing. The fish-hook penetrated the sclera, passed the trabecular meshwork, and exited into the anterior chamber. He underwent surgery under local anesthesia to remove the intraocular foreign body and to repair the wound. The hook was removed backing through the entrance wound, enlarge the primary scleral laceration. Final visual outcome, one month after trauma, was 0.0 LogMar. Conclusions and Relevance . Our unusual case shows a modified extraction technique of fish-hook from the eye. Although the fish-hook injury represents generally a serious occurrence, in some cases, a prompt and appropriate method of extraction can lead to a good final outcome.